How to improve antibiotic awareness campaigns: findings of a WHO global survey - Benedikt Huttner; Mirko Saam; Lorenzo Moja; Karen Mah; Marc Sprenger; Stephan Harbarth; Nicola Magrini (BMJ Global Health)
Introduction We aimed to examine the characteristics of antibiotic awareness campaigns (AAC) conducted on a national or regional level since 2010.Methods In October 2016, the WHO invited stakeholders involved in the planning or conduct of AACs to answer a web questionnaire. We solicited general information about the characteristics of the AAC, with a particular focus on key messages supporting optimal use of antibiotics.Results Stakeholders in 93 countries were contacted and 55 countries responded. Overall, 60 AACs from 16 low/middle-income countries (LMIC) and 31 high-income countries were identified. Forty-five campaigns (75%) were conducted on a national level and most of them (47/60; 78%) were organised by public health authorities and publicly funded. There were no major differences between LMICs and high-income countries in the types of key messages. The scientifically questionable ‘Finish your prescription’ slogan was used by 31 AACs (52%). A One Health approach was mentioned in 13/60 AACs (22%). Most messages were universally applicable; adaptation to locally prevalent public misconceptions was not systematic. The evaluation of the impact of campaigns was still incomplete, as only 18 AACs (30%) assessed their impact on antibiotic use.Conclusion For future AACs, it seems essential to base messages more rigorously on scientific evidence, context specificities and behavioural change theory. A new generation of messages that encourage first-choice use of narrow spectrum antibiotics is needed, reflecting international efforts to preserve broad spectrum antibiotic classes. Evaluation of the impact of AACs remains suboptimal.